PEMBELAJARAN KONTEKSTUAL PADA ERA PANDEMI COVID-19 - Abdul Manaf (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2020)
This study aimed to examine the implementation of contextual learning in higher education during the COVID-19 pandemic based on scientific articles published in 2020. The study employed a qualitative approach using a literature review method. The data sources consisted of ten scientific articles focusing on higher education learning during the COVID-19 pandemic and selected based on their relevance to the research topic. Data were collected through document analysis and analyzed using content analysis techniques, including data reduction, data presentation, synthesis, and conclusion drawing. The implementation of contextual learning, supported by digital Platforms such as Learning Management Systems (LMS), Zoom, Google Classroom, and Microsoft Teams, improved students' learning motivation, active participation, critical thinking, problem-solving skills, and independent learning. Although several challenges remained, including limited internet access, technological readiness, and restricted interaction, the reviewed studies consistently demonstrated that contextual learning contributed positively to the quality of higher education during the COVID-19 pandemic. Therefore, it can be concluded that contextual learning is an effective approach to promoting meaningful, active, and student-centered learning in higher education during the COVID-19 pandemic.